2006
DOI: 10.1038/sj.onc.1210152
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of BCL11B expression leads to apoptosis of malignant but not normal mature T cells

Abstract: The B-cell chronic lymphocytic leukemia (CLL)/lymphoma 11B gene (BCL11B) encodes a Kru¨ppel-like zincfinger protein, which plays a crucial role in thymopoiesis and has been associated with hematopoietic malignancies. It was hypothesized that BCL11B may act as a tumorsuppressor gene, but its precise function has not yet been elucidated. Here, we demonstrate that the survival of human T-cell leukemia and lymphoma cell lines is critically dependent on Bcl11b. Suppression of Bcl11b by RNA interference selectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 35 publications
8
72
0
2
Order By: Relevance
“…Our findings are in accordance with the known antiapoptotic role of BCL11B in T-cell malignancies (18)(19)(20). Recently, it has been shown that BCL11B is one of the necessary genes for T-cell differentiation and is associated with T-cell malignancies (21)(22)(23).…”
Section: Discussionsupporting
confidence: 79%
“…Our findings are in accordance with the known antiapoptotic role of BCL11B in T-cell malignancies (18)(19)(20). Recently, it has been shown that BCL11B is one of the necessary genes for T-cell differentiation and is associated with T-cell malignancies (21)(22)(23).…”
Section: Discussionsupporting
confidence: 79%
“…RP11-179F4 (gain: 3 cases; high-level amplification: 2 cases) was found to contain BCL11B, which has been implicated in lymphoid malignancy (13,19,20). Three consecutive BAC clones at 9p21.3 were identified as regions of recurrent homozygous loss (Table 3).…”
Section: Frequencymentioning
confidence: 99%
“…On the other hand, Bcl11b +/-heterozygous mice appear normal but are susceptible to thymic lymphomas when they are subjected to gamma radiation [15]. In in vitro studies, selective inhibition of BCL11B in Jurkat cells leads to cell cycle arrest and apoptosis [12,16]. These data suggest that BCL11B is involved in differentiation, cell proliferation and survival in different cell types.…”
Section: Introductionmentioning
confidence: 82%